A multicenter randomized, double-blind, placebo-controlled trial to evaluate the safety and efficacy of rhubarb in treating acute exacerbation of chronic obstructive pulmonary disease of the syndrome type phlegm-heat obstructing the lungs - Fengjie Zheng; Yan Sun; Xianggen Zhong; Yueqi Wang; Ruohan Wu; Miao Liu; Yuchao Liu; Kuo Gao; Yuhang Li (Journal of Traditional Chinese Medical Sciences, 2016)
Objective: To observe the clinical efficacy and safety of oral administration of the traditional Chinese herb rhubarb to treat acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Method: This was a multicenter randomized double-blinded placebo controlled study that took place in 7 provinces of China that enrolled 244 patients (aged 18–80 years) who had acute exacerbation of COPD with the traditional Chinese syndrome pattern of phlegm-heat obstructing lung. Participants were divided into experimental and control groups. The experimental group received 4.5 g of rhubarb granules twice daily and the control group received placebo granules. Both groups also received conventional Western therapy consisting of oxygen therapy, an antibiotic, expectorant, and a bronchodilator. Treatment lasted 10 days. Symptom scores for cough, sputum volume and color, wheezing and chest tightness before treatment and on days 3, 5, 7, and 10 during the treatment were recorded. Lung function, arterial blood gas and levels of serum inflammatory factors, interleukin-4 (IL-4), interleukin-8 (IL-8), and interleukin-10 (IL-10) and tumor necrosis factor-alpha (TNF-α), before and after treatment were measured. Results: The sample size of the full analysis set (FAS) was 244 participants, and the sample size of per protocol set (PPS) was 235. Following 10 days' treatment, symptom scores of the experimental group were markedly lower than those of the placebo group (FAS: mean difference −1.67, 95% CI: –2.66 to −0.69, P = 0.001; PPS: mean difference −1.55, 95% CI: −2.56 to −0.54, P = 0.003). Lung function in the experimental group was significantly higher than in the placebo group (FEV1, FAS: mean difference 0.12, 95% CI: 0.06 to 0.18; P < 0.001; PPS: mean difference 0.12, 95% CI 0.05 to 0.18; P < 0.001. FVC: FAS: mean difference 0.16, 95% CI: 0.06 to 0.26; P = 0.002; PPS: mean difference 0.16, 95% CI 0.05 to 0.26; P = 0.003. FEV1%, FAS: mean difference 5.95, 95% CI: 3.36 to 8.53; P < 0.001; PPS: mean difference 5.92, 95% CI 3.28 to 8.56; P < 0.001.). PaO2, PaCO2, as well as serum inflammatory factors were also improved when compared to the placebo group. There were no significant differences in the incidence rate of adverse reaction between the two groups. Conclusions: Compared with placebo, rhubarb granules significantly reduced symptom scores, improved blood oxygen level, controlled systemic inflammatory response, without significant adverse effects. Thus, rhubarb may be a beneficial adjuvant method for treating the phlegm-heat obstructing the lung syndrome pattern of AECOPD.